Two very different brothers: a comparison of the Chile and Argentina cases - Aravena Lavín, Pedro (Estudios Internacionales, 2012)
Argentina has one of the highest standards of support for democracy in Latin America despite the economic crises of recent decades while Chile, despite being one of the most economically successful countries in the region, has a poor support for democracy. This article presents a comparison of ordered logistic regression analysis of the year 1997 with the year 2001. In addition, such models are complemented with respect to the political culture in both countries. Economic stability, income distribution, interpersonal trust, interest in politics and civic education are more significant factors in the Argentinean than in the Chilean case. There is a strong polarisation between the political orientation of left and right in Chile with regard to the support of democracy.